Vous êtes sur la page 1sur 4

# :

:
. .

: 1
f x0 ) . lim f (x) = f (x0

: 1
( 1 :

x+3
x5

x3 8
,
)lim ( x 3 2 x + 1
x2 x 2
x 1
x 5
x +1 2
2 sin( x) x
lim
. lim
,

x3 1
x

0
3
x

x
x2 9
; x 1
= ) f ( x
x0 = 1 ,
(1
x 1

( 2 f g IR :
f (1) = 3

x x2 1
3

; x 1
= ) f ( x
= ) g ( x
; x 1

x + 1 1
x

x
=

f
(
x
)
;
x
0

g (1) = 2
f ( x) = 3x ; x1
x
x0 = 0 ,
(2

f ( 0) = 1
f g . x0 = 1

2
___________________________________________
( 3 x0 = 1
: 2
, y = x f
lim

( 1 f ( x ) 0 :
( 2 f ( x ) x :

lim+

xx0

f
x0 .

x0 = 1
________________________________________
: 2
f x0 ) . lim+ f ( x) = f ( x0

( 3 f ,
.
x x0
( . f
f x0 ) lim f ( x) = f ( x0
x x0
___________________________________________
:3
f ( x) = x 1 ; x 1
f
:

(
1

IR

2
f ( x) = ( x 1) ; x1
: g
f . 1
]I 4 = [1,+[ , I 3 = [ 1,2] , I 2 = [ 1,0[ , I1 = [0,2
( 2 f x :
f ( x) = x x 2 ; x1

f ( x) = x 1 x 2 1 ; x 1
( 3 f IR :

1 + sin( x) 1
; x0
= ) f ( x
x

f ( x) = 1 + x 1 ; x 0

2
. x0 = 0

cherifalix@yahoo.fr

:
:

:
. .

.
:3
f ][ 2;5

:3
f I :

(1

(2

f ( x) = x x 2 ; x 2

; I = IR

3
f
x
x
(
)
=
;

3 x

2
)f (x ) = x. sin ; (x 0
; I = IR
x

f (0) = 0

f ( x) = cos(4 x 2 + 3x 1) ; I = IR
(3
________________________________________
:4
I f :
]f ( x) = x + 1 ; I = [ 1;3
(1
( 1
2
(2
]f ( x) = x + 1 ; I = [ 1;2

f ( x) = 2 x 3 ; x 2
; I = [ ;4] ( 3
I
I

2
f ( x) = x 3 ; x 2
][ 2;1
________________________________________
][ 1;2
:5
][2;4
: I
][4;5
(E ) : x 3 3x 2 + 15 x 7 = 0 ; I = IR
(1
2
___________________________________
(E ) :1 + sin (x ) x = 0 ; I = IR
( 2
:4
(E ) : x 4 + 2 x 3 = 0 ; I = 1 ; 2 ( 3
f ] I = [1;3 :
2

f ( x) = x 2 2 x
________________________________________
( 1 f . J
:6
f J
( 2 J I . f
I :
(3 x J y I
f ( x) = 2 x + 3 ; I = IR
(1
:
f ( y) = x y = 1 + x + 1
2x + 3
= )f ( x
___________________________________________ ( 2
[; I = ]1;+
x 1

: 1
[f ( x) = 2 x x ; I = ]0;1
(3
:

________________________________________
2
f ( x) = 2 x 3 x ; x1
:7

( I :
2
f ( x) = x + 4 ; 1 x1
3
4
1024 .5 3200000
9 . 3 3.3 9

2
=A
=, B
f ( x) = x + 1 + 2 ; x 1
3
4
5
64 . 256 . 18
81.
3
1 - 1 . 0
2
___________________________________________
3
4 . 8 5 2
:2

=C
IR :
3
4
f ( x) = x x 2 ; x 2

3
; x 2
= ) f ( x
3 x

cherifalix@yahoo.fr
f IR

:
. .

.
:8
f :
3
2+ x
1
= )f ( x
, f ( x) = 4 1 , f ( x) = 3 x 2 + 2 x 3
3
x
2 x
_________________________________________
:9
:
3
4
x +1 x +1
(1
=
lim 6
x +
x +1 + x +1

(2

(x + 1)2 + x 2 + x

= .12 x

x +1
x +1 4 x

lim

x 1
4

lim

(3
x +1 x
_________________________________________

: 1
f :
sin x

,x 0
= ) f ( x
1+ x 1 x

f (0) = 1

-1 . f
-2 f . 0
_________________________________________
: 2
+
f IR :

1 3 x
[, x [0,1[ ]1,+
= ) f ( x
x 1

f (1) = 1

3
. IR +
_________________________________________
:3
:

x3 + x
x 1

x + 3

(x ]1,+[); f ( x) = 1
1
x 1

f (x ) = x +

( g IR :
g (x ) = f (x ) x
g (a ) 0 : . g (b ) 0
( f ( x ) = 0
[. ]0;1
_________________________________________
:5
f x :
f (x ) = x + x + 3
( 1 D f . f
( 2 f . D f
( 3 f
.
1
( 4 ) f ( x x . J
( 5 ) f 1 ( x ) = f ( x
[. [ 3;+
_________________________________________
:6
f [ ]1;+ :
2 x3
x3 1

= ) f (x

( 1 :
2
x ]1;+[ ; f (x ) = 2 + 3
x 1
( f [. ]1;+
( f J
[. ]1;+
( 2 ( . f 1
( ) f 1 ( x x . J
_________________________________________
:7
f (x ) = 3 x 2 + x
f :
( 1 - D f . f
( :

( 1 :
) f (x
lim
) lim f ( x ) lim f ( x ) lim ( f (x ) x
1
x
x
x +
x +
x

( 2 = x :
x 1
( f (x ) = x ][1;2
[. ]1;2
( 2 g f ]I = ] ;1
2
( 3 . ( 2 ) = 1 :
( a b a b g (a ) g (b ) : I
_________________________________________ ( g g 1 J
:4
I

a
,
IR

f
( ) g 1 ( x x J
[ ]0;1 f (a ) = 0 f (b ) = 1
cherifalix@yahoo.fr

:
:

:
. .

.
2008/2007